Study of VCAM-1 Gene Expression in Normal and Tumoral Tissues in Patients with Colorectal Cancer - Siyasi Mahdiyeh; Mahjoubi Frouzandeh; Mahjoubi Bahar; Shabani Samira (Journal of Biotechnology and Biomedical Science, 2017)
Aim: Colorectal cancer is one of the most commonly diagnosed cancers in the world. Cell adhesion molecules play an important role in the progression of various cancers. It has been shown that the high level expression of some Cell adhesion molecule could be a new diagnostic factor for several cancers. Vascular cell adhesion molecule 1(VCAM1) is a cell surface glycoprotein that is expressed in the endothelium activated by cytokine. Generally, VCAM-1 expression level is very poor in normal adult tissue endothelial cells. According to the above explanation, this study was conducted to investigate the expression of VCAM-1 in tumoral tissues and adjacent normal tissues in Iranian colorectal cancer patients to its relation with clinicopathological Features in patients with cancer. Methods: In this study, 60 tumoral tissues and 39 adjacent normal tumor tissues were evaluated using reverse transcription-polymerase chain reaction (RT-PCR) technique. Conclusion: A significant correlation was found between VCAM-1 expression level and the stage, lymph nodes involvement, tumor progression factor of cancer and sex. Interestingly, VCAM-1 expression not observed in tumors with stage0. No association was seen between VCAM-1 expression and other clinical features such as age, size of the tumor, metastasis and the number of lymph nodes. These findings suggest that VCAM-1 expression level may reflected disease progression and elevation in VCAM-1 has prognostic significance in patients with colorectal carcinoma.
Keywords: colorectal cancer